Tinjauan Hukum Pelaksanaan Salat Id di Beberapa Masjid yang Berdekatan dalam Satu Wilayah - Dain Yunta, Akhmad Hanafi (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2019)
This study aimed to discuss the legal review relating to the place to perform Id prayer, those are: (1) the place to perform Idprayer; and (2) performing Id prayer at more than one places in one area or district, then it would be connected with the intent and purpose of the unity of the people. This research employed a qualitative-descriptive approach with library research methods. The result shows that: (1) Id prayer is one form of jama'iyyah worship whose purpose is same as the other jama'iyyah worship which is to train the Muslims to unite especially when there is a justified difference in order to maintain the ukhuwah and unity of the people; (2) The phenomenon of praying Id in many places that are close together is something that must be addressed properly, spesifically by the scholars and parties who have authority in regulating this matter. Most scholars view that the the preferred one is in mushalla (field/open place) that can accommodate many people in that area and Id prayer is performed at only one place, unless there is necessity that Id prayer be performed in different places in one area/district. This confirms that the unity of the people is very important and becomes the main goal in the performance of Id prayer.